Sistem Informasi Absensi Berdasarkan Titik Lokasi Menggunakan Metode Waterfall Berbasis Web - Sonia Natasyah; Yogisaputra; Ricky Alfonsus Situmorang; Ika Devi Perwitasari (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Time attendance is a crucial aspect of human resource management that is often faced with accuracy and efficiency challenges. This research identifies the main problems in traditional attendance systems that often suffer from data inaccuracies and time-consuming manual processes. To overcome these problems, this research aims to design and develop a website-based attendance information system that utilizes location points (geolocation) as the basis for attendance validation. The software development method used is the Waterfall method, which consists of the stages of requirements analysis, system design, development, testing, and implementation. The Waterfall method was chosen because it provides a clear structure and systematic sequence of steps, facilitates the creation of a well-structured system and is easy to implement. This research applies web technology to build a system that enables attendance monitoring based on the user's geographical location. The results show that the system successfully integrates geolocation features with the attendance database effectively, improving the accuracy of attendance data and reducing the time and effort required for the attendance process. The system also offers a user-friendly interface, allowing users to perform attendance easily through mobile devices. The results of the Usability value calculation get a total score of 1,721 with a percentage result of 86% then converted into a qualitative scale. The result of the value conversion is “Very Good” and has met Usability standards. This finding is expected to increase efficiency and accuracy in attendance management in various organizations.